2019
DOI: 10.1038/s41598-019-51911-5
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Induced Pluripotent Stem Cells towards Mesenchymal Stromal Cells is Hampered by Culture in 3D Hydrogels

Abstract: Directed differentiation of induced pluripotent stem cells (iPSCs) towards specific lineages remains a major challenge in regenerative medicine, while there is a growing perception that this process can be influenced by the three-dimensional environment. In this study, we investigated whether iPSCs can differentiate towards mesenchymal stromal cells (MSCs) when embedded into fibrin hydrogels to enable a one-step differentiation procedure within a scaffold. Differentiation of iPSCs on tissue culture plastic or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…In fact, iPSCs differentiated into induced mesenchymal stem cells (iMSCs) in the 2D condition and were a closer match to primary MSC than the 3D differentiated cells. The cells differentiated in 3D had a notable upregulation of genes related to the cardiovascular system and neurogenesis (61). These results indicate that even though 3D systems are more physiologically relevant and represent an increased complexity compared to 2D systems, these platforms still need further optimization to be more physiologically precise.…”
Section: Patient-derived Cells For Studying Respiratory Diseasementioning
confidence: 93%
“…In fact, iPSCs differentiated into induced mesenchymal stem cells (iMSCs) in the 2D condition and were a closer match to primary MSC than the 3D differentiated cells. The cells differentiated in 3D had a notable upregulation of genes related to the cardiovascular system and neurogenesis (61). These results indicate that even though 3D systems are more physiologically relevant and represent an increased complexity compared to 2D systems, these platforms still need further optimization to be more physiologically precise.…”
Section: Patient-derived Cells For Studying Respiratory Diseasementioning
confidence: 93%
“…Induced pluripotent stem cell (iPSC) differentiates into a typical MSC-like phenotype on tissue culture plastic or on the surface of fibrin hydrogels. In contrast, iPSCs embedded in a 3D environment do not differentiate towards MSC and have reduced differentiation potential for osteogenic and lipogenic lineages [ 27 ].…”
Section: Mechanical Microenvironment For Stem Cell Growthmentioning
confidence: 99%
“…However, directing iPSCs to a specific cell lineage remains a challenge and each differentiation progress likely requires unique features in the culture system. While a 3D culture system is favorable to the generation of many other cell types, a recent study has shown that it may impair the differentiation of iPSCs towards mesenchymal stem cells-like phenotype as compared to a 2D culture system ( Goetzke et al, 2019 ). iPSCs are equally suitable for all the biomedical applications of ESCs, such as drug screening, toxicological studies, disease modeling and cell therapies.…”
Section: Stem Cellsmentioning
confidence: 99%